Selamatkan Ginjalku, Edukasi Bahaya Jajanan Tidak Sehat sebagai Upaya Pencegahan Gangguan Fungsi Ginjal pada Siswa Sekolah Dasar - Azizah, Nurul; Tamina Melindah; Ega Delva; Ni Ny. Wedarthani Achintya A. (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service program was implemented to address the increasing risk of kidney function disorders among school-aged children, which is closely related to the high consumption of unhealthy snacks high in sodium, sugar, synthetic additives, and preservatives. The activity aimed to enhance students practical knowledge in identifying and avoiding unhealthy snacks as an early preventive effort for kidney damage. The program was conducted at SDN 84 Parepare involving 35 sixth-grade students through several stages, including preparation, interactive health education, role-play sessions, and group discussions. Educational media such as posters, demonstration tools, and visual presentations were utilized to support the learning process. The results showed that most students initially had limited understanding of the link between unhealthy snacks and kidney health, with 80% reporting frequent consumption of snacks without considering hygiene or nutritional content. After the intervention, students demonstrated improved awareness, actively engaged in discussions, and were able to identify healthier food options. The interactive learning approach, combined with visual aids and storytelling, effectively increased students’ comprehension and interest in adopting healthier eating habits. This program highlights the importance of continuous school-based nutrition education as a promotive and preventive measure to support children’s kidney health.